Revealing the Secrets of RUN and QPS: New Trends for Optimal Real-Time Multiprocessor Scheduling - Massa, Ernesto; Lima, George; Regnier, Paul (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
Until recently there has been a common belief that optimal multiprocessor real-time scheduling algorithms necessarily incur a high number of task preemptions and migrations. New scheduling algorithms have shown that this is not the case. In this paper we explain why two of these algorithms, RUN and QPS, achieve optimality with only a few preemptions and migrations. We also compare these two algorithms, exhibiting their similarities and differences. By putting RUN and QPS side-by-side, we bring about their fundamental properties and help in the understanding of the multiprocessor real-time scheduling problem.